Energy and US foreign policy the quest for resource security after the Cold War - Mahdi, Ahmed (International library of security studies ;, 2012)
The author demonstrates how and why oil has played a central role in US relations with the wider world. He builds a compelling picture of America trying, and failing, to secure its energy supplies with enormous and sobering consequences; Washington's quest for oil has actually weakened and undermined its global influence and destabilized the world' economic prosperity and security.